2007
DOI: 10.1021/la070140n
|View full text |Cite
|
Sign up to set email alerts
|

Selective Intercalation of Polymers in Carbon Nanotubes

Abstract: A room-temperature, open-air method is devised to selectively intercalate relatively low-molecular-weight polymers (approximately 10-100 kDa) from dilute, volatile solutions into open-end, as-grown, wettable carbon nanotubes with 50-100 nm diameters. The method relies on a novel self-sustained diffusion mechanism driving polymers from dilute volatile solutions into carbon nanotubes and concentrating them there. Relatively low-molecular-weight polymers, such as poly(ethylene oxide) (PEO, 600 kDa) and poly(capro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…Owing to the intrinsic hollow properties of carbon nanotubes (CNTs), Yarin and co-workers found that a low-molecular-weight polymer solution could enter into CNTs and form segmented or foamed inner structures. [133] They utilized a kind of open-ended wettable CNT as target. When the CNTs were immersed in a dilute solution of low-molecular-weight polymer, the polymer will enter into the CNTs and concentrate in the CNTs driven by a self-sustained diffusion mechanism.…”
Section: Segmented Tubesmentioning
confidence: 99%
“…Owing to the intrinsic hollow properties of carbon nanotubes (CNTs), Yarin and co-workers found that a low-molecular-weight polymer solution could enter into CNTs and form segmented or foamed inner structures. [133] They utilized a kind of open-ended wettable CNT as target. When the CNTs were immersed in a dilute solution of low-molecular-weight polymer, the polymer will enter into the CNTs and concentrate in the CNTs driven by a self-sustained diffusion mechanism.…”
Section: Segmented Tubesmentioning
confidence: 99%
“…Relatively, low molecular weight polymers, such as poly(ethylene oxide) (PEO, 600 kDa) and poly(caprolactone) (PCL, 80 kDa), were encapsulated in MWNTs [59] ( Table 12.2). TEM images reveal foam and peapod-like patterns of the dried polymer in the nanotube channels.…”
Section: Molecules Without Metal Atomsmentioning
confidence: 99%
“…In other cases, CNT forest microfeatures (e.g., a pillar of square cross-section) having aspect ratios close to 1 are densified by the solvent to create higher-volume-fraction microfeatures. [31,40] Capillarity-driven patterning is well reviewed [32,41,42] and the degree of wetting and densification are noted to be a function of the contact (or wetting) angle of the liquid with the CNTs, the liquid's viscosity, and CNT characteristics (diameter, volume fraction). Solvent-induced densification was also explored in this work using isopropyl alcohol, and the resulting forests were highly contracted, irregular, and contained micrometer-scale cells as observed by others.…”
mentioning
confidence: 99%